Quantifying the Impact of Surface Ozone on Human Health and Crop Yields in China - Yi Cui; Jiayan Wang; Jinghan Wang; Mingjie Kang; Hui Zhao (Atmosphere)
In recent years, surface ozone (O3) pollution has emerged as a significant barrier to the continued improvement of air quality in China, making O3 risk assessment a critical research priority. Using nationwide O3 monitoring data, this research investigated the spatial characteristics of O3 pollution and assessed its potential impacts on human health and crop yields. The results showed that the maximum daily 8 h average O3 (MDA8 O3) exhibited higher concentrations in eastern and northern regions, and lower concentrations in the western and southern regions of China. Long-term O3 exposure was associated with an estimated 175,154 all-cause deaths nationwide, with the highest health risks observed in Shandong, Henan, and Jiangsu provinces. The AOT40 values for the winter wheat and single-rice growing seasons in China were 9.30 × 103 ppb·h and 1.29 × 104 ppb·h, respectively. Moreover, O3 exposure led to relative yield losses of 22.1% for winter wheat and 9.3% for single rice, corresponding to crop yield losses (CPLs) of 63 million metric tons and 14 million metric tons, respectively. Higher winter wheat CPL values were primarily concentrated in Henan, Shandong, and Hebei, while higher single rice CPL values were observed in Jiangsu, Hubei, and Anhui. This study presents a novel coupling of O3 pollution exposure with human health and agricultural risk assessments across China, emphasizing the need for region-specific O3 management strategies to protect public health and ensure agricultural sustainability. In conclusion, this study highlights the importance of targeted O3 control in densely populated and major crop-producing areas to mitigate health risks and yield losses, thus safeguarding ecosystem health and food security.